A collective, undifferentiated accounting profession: an Australian study - Inglis, R.; Shelly, M.; Morley, C.; De Lange, Paul (Wiley-Blackwell Publishing Asia, 2011)
A study of 386 potential and current members of the accounting profession inAustralia and South-East Asia provides evidence of the importance of threeattributes – brand/reputation, international recognition of qualifications andcareer opportunities – in the decision to join a professional accounting body.While these attributes are important, logit regression models indicate that theyare not discriminatory in the choice of professional body and suggest a perceptionof a collective, undifferentiated accounting profession. The marketing ofbrand/reputation and membership benefits may be a more efficient and effectivestrategy in attracting members and differentiating the profession if undertakenby a combined or coordinated professional body.